Leveraging brand image in the cosmetics market : how premium brands create the illusion of luxury - Loewenthal, Elizabete Helena Félix da Silva Friman (2020)
The luxury business model is in its own league when compared to other more common types of business models. It allows for several benefits for companies that apply it, one of these benefits being boosted brand image. The purpose of this thesis is to show how non-luxury companies can use this business model and successfully adapt it in a way that boosts brand image, specifically for the market of cosmetics. While the idea that adopting this business model outside of luxury companies is not new, choosing a specific market such as cosmetics and analyzing how exactly this sort of leverage can be achieved had yet to be developed, meaning that its practical value was unproven. A qualitative approach was taken relying on a multiple case study of three premium cosmetics brands, Natasha Denona, NARS Cosmetics and Fenty Beauty, who are considered to be main players in the market and successful. Through this research, I found that these three brands leverage brand image through the application of the luxury business model, using distinct pricing strategies and communicating in a way that allows them to create the illusion of luxury.